Study on Functional Mechanical Performance of Honeycomb Array Structures Inspired by Gideon Beetle - Liu, Ruiyao; Yao, Guofeng; Xu, Zezhou; Guo, Xue; Gao, Kuiyang; Cao, Qing; Yu, Zhenglei; Zhang, Zhihui; Han, Chunyang; Liu, Jiabao (Journal of bionics engineering, 2022)
To obtain bio-inspired structures with superior biological function, four bio-inspired structures named regular arrangement honeycomb structure (RAHS), staggered arrangement honeycomb structure (SAHS), floral arrangement honeycomb structure (FLAHS) and functional arrangement honeycomb structure (FUAHS) are designed by observing the microstructure of the Gideon beetle, based on the optimal size bio-inspired cells by response surface method (RSM) and particle swarm optimization (PSO) algorithm. According to Euler theory and buckling failure theory, compression deformation properties of bio-inspired structures are explained. Experiments and simulations further verify the accuracy of theoretical analysis results. The results show that energy absorption of FLAHS is, respectively, increased by 26.95%, 22.85%, and 121.45%, compared with RAHS, SAHS, and FUAHS. Elastic modulus of FLAHS is 110.37%, 110.37%, and 230.56% of RAHS, SAHS, and FUAHS, respectively. FLAHS perfectly inherits crashworthiness and energy absorption properties of the Gideon beetle, and FLAHS has the most stable force. Similarly, RAHS, SAHS, and FUAHS, respectively, inherit mechanical properties of the Gideon beetle top horn, the Gideon beetle middle horn, and the abdomen of the beetle. This method, designing bio-inspired structures with biological functions, can be introduced into the engineering field requiring the special function.